Effect of (−)-epigallocatechin gallate at different pH conditions on enteric viruses. (August 2017) - Falcó, Irene; Randazzo, Walter; Gómez-Mascaraque, Laura; Aznar, Rosa; López-Rubio, Amparo; Sánchez, Gloria
Abstract: Epigallocatechin gallate (EGCG), a flavonoid from green tea, is said to have extensive antimicrobial activity in a wide range of food spoilage or pathogenic fungi, yeast and bacteria. In this work, the antiviral activity of EGCG was assessed against hepatitis A virus (HAV) and murine norovirus (MNV), a human norovirus surrogate, at different temperatures, contact times and pH conditions by cell-culture methods. EGCG was effective in reducing the titers of HAV and MNV in a dose-dependent manner at neutral pH and 25 and 37 °C, while no effect was reported at 4 °C. HAV and MNV infectivity was completely removed after overnight treatment with EGCG at 2.5 mg/mL at 37 °C. Furthermore, results also revealed that EGCG was very effective inactivating MNV and HAV at neutral and alkaline pH but was ineffective at pH 5.5. Results from cell-culture assays and viability RT-qPCR assays indicated that EGCG did not dramatically affect viral capsid, which instead may suffer subtle alterations of proteins. Moreover, HPLC/MS analysis of catechin solutions at different pHs indicated that antiviral activity was most likely due to catechin derivatives rather than EGCG itself, given the evolution of these compounds at the various pH conditions tested. These findings suggest that green tea catechins appear to be a suitable natural option for foodborne viral reduction. Highlights: EGCG has antiviral activity which increases as pH increase. EGCG did not dramatically affect viral capsid. HPLC analysis shows that antiviral activity was most likely due to EGCG derivatives.